Analysis Of Factors Causing Burnout At Karya Medika Hospital, Bantar Gebang, Bekasi In 2024 - Hanum, Nida Najibah; Ulfa, Laila; Nugraha, Susiana; Agustin, Dinni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
Burnout is a condition of physical or mental and emotional exhaustion. Demands towards quality for health services are required to be addressed with improvement of the healthiness of the healthcare workers. Every healthcare professional who experienced burnout can be identified by acknowledging a decreased performance in providing health services. This research aims to identify the correlation between age, genders, years of services, years of education, type of work, work satisfaction, pay satisfaction and leadership qualities towards burnout. Method of research used quantitative approaches with cross-sectional design. 217 total respondents population are sampled to 165 respondents. Instruments utilized are MBI, MSQ, PSQ, and MLQ with language translation method of back translation. Data analysed using multiple logistic regression. Results of this research are 48% health workers are in high degree burnout, while the rest 51% are low degree burnout. Following the parameters determined are ≤ 30 years (59%), male genders (47%), years of services >2 years (47%), years of education >15 years (46%), health professionals (57%), work satisfaction (55%), salary satisfaction (58%), effective leadership style (59%) are higher chances to be in a burnout condition. The result of multivariate analysis shows that there are 2 most affecting variables towards burnout; >30 years (p=0.011, OR = 0.406) and effective leadership quality (p=0.031, OR=0.400). Conclusion of this research shows that >30 years and effective leadership style are the protective factors of how employees stated in burnout condition. Hospital is suggested to accommodate this by implementing stress management programs and work-life balance and provide training of leadership qualities to create more healthy working environments and reduce the chance of having burnout. Keyword: burnout, hospital, age, leadership style